Angels of (Queer) Histories: Synaesthetic Films by Anatoly Belov and Oksana Kazmina - Dmytryk, Olena Syaivo (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2025)
This essay studies the interconnection between senses, affect and (queer) histories and politics in the films of Anatoly Belov and Oksana Kazmina. It does so by addressing the ‘synaesthetic’ quality of these works: the aesthetics foregrounding the symbiosis of different senses. I argue that by constructing a sensory cinematic experience, the films aim to move and re-orient the audience, altering consciousness and fostering solidarities. Through a close reading of selected titles, I examine the entanglement of sound, visuality, and touch in Seks, likuval’ne, rok-n-rol/ Sex, Medicated, Rock-n-Roll (2013, Ukraine) and Sviato zhyttia / The Feast of Life (2015, Ukraine) within the context of broader historical shifts in Ukraine. Drawing on the concepts of Walter Benjamin and Raymond Williams, I consider films by Belov and Kazmina as works that capture emerging structures of feeling and experiment with multiple temporalities. Янголи (квір-)історій: синестезійні фільми Анатолія Бєлова та Оксани Казьміної Анотація: У статті досліджується взаємозв’язок між чуттями, афектом і (квір-)історіями та політиками у фільмах Анатолія Бєлова й Оксани Казьміної. Аналіз ґрунтується на осмисленні «синестезійної» якості цих робіт, тобто естетики, яка висуває на передній план симбіоз різних відчуттів. Я стверджую, що, через вибудовування чуттєвого кінематографічного досвіду, ці фільми прагнуть зворушити й переорієнтувати глядача, змінюючи свідомість і сприяючи формуванню солідарностей. Я ретельно аналізую переплетення звуку, візуальності та дотику у фільмах Секс, лікувальне, рок-н-рол / Sex, Medicated, Rock-n-Roll (2013, Україна) та Свято життя / The Feast of Life (2015, Україна) в контексті ширших історичних змін в Україні. Спираючись на концепції Вальтера Беньяміна та Реймонда Вільямса, я розглядаю фільми Бєлова ій Казьміної як твори, що фіксують зародження «структур почуттів» і експериментують із множинними темпоральностями. Ключові слова: Анатолій Бєлов; Оксана Казьміна; Людська подоба; синестезія; гаптична естетика; квір-кіно; структури почуттів; українське кіно; сучасне українське мистецтво; електронна музика; російсько-українська війна